Immunohistochemistry Staining for the Mismatch Repair Proteins in Endometrial Cancer Patients - Pimpitcha Puangsricharoen; Tarinee Manchana; Chai Ariyasriwatana; Surang Triratanachat (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: Lynch syndrome (LS) increases the lifetime risks of endometrial cancer by approximately 40-60%. Although universal screening with immunohistochemistry (IHC) for mismatch repair (MMR) proteins has been recommended, it is not yet common in Thailand. This study aimed to evaluate the prevalence of MMR deficiency and identify patients who may be at risk for LS. Materials and Methods: IHC for MMR proteins, including mutL homolog 1 (MLH1), mutS homolog 2 (MSH2), mutS homolog 6 (MSH6), and PMS1 homolog 2 (PMS2), were tested in 156 endometrial cancer patients who underwent primary surgery between 2013-2015. This study also screened for the revised Bethesda guidelines, using age at diagnosis and personal and family history of LS-related cancers as variables.Results: Fifty-seven of 156 (35.9%) patients had MMR deficiency; 42 experienced losses of MLH1 and PMS2, 10 experienced losses of MSH2 and MSH6, and 5 experienced a loss of MSH6 expression. Only 36 patients (23.1%) met the revised Bethesda guidelines; 29 patients (18.6%) were diagnosed earlier than age 50; 10 patients (6.4%) had synchronous colon or ovarian cancer; and only 13 patients (8.3%) possessed a family history of LS-related cancers. It was possible to detect MMR deficiency in 41/120 patients (34.2%) who did not meet the revised Bethesda guidelines. Conclusion: MMR deficiency as a result of IHC can be detected in 35.9% of endometrial cancer patients. However, it was still possible to detect MMR deficiency in at least one-third of patients who did not meet the Bethesda guidelines. Screening endometrial cancer patients for MMR IHC should be considered, with the aim of diagnosing and preventing LS-related cancers in both patients and their relatives.